The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1038/cddis.2012.133
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-ray irradiation promotes premature meiosis of spontaneously differentiating testis–ova in the testis of p53-deficient medaka (Oryzias latipes)

Abstract: In this study, the roles of p53 in impaired spermatogenic male germ cells of p53-deficient medaka were investigated by analyzing histological changes, and gene expressions of 42Sp50, Oct 4 and vitellogenin (VTG2) by RT-PCR or in situ hybridization in the testes. We found that a small number of oocyte-like cells (testis–ova) differentiated spontaneously in the cysts of type A and early type B spermatogonia in the p53-deficient testes, in contrast to the wild-type (wt) testes in which testis–ova were never found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…This family of proteins play very important roles in cell differentiation stemness and plasticity, 30, 31, 32, 33 in immune response regulation, 34 in tumorigenesis and tumor suppression, 33, 35, 36, 37, 38 in development and reproduction, 39, 40 DNA damage, 41 and apoptosis and cell-cycle regulation. 33, 42, 43 In addition to regulating each other's function, 37, 44, 45 the functional outcome of these proteins are regulated by different mechanisms, including miRNAs, post-translational modifications, and protein–protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…This family of proteins play very important roles in cell differentiation stemness and plasticity, 30, 31, 32, 33 in immune response regulation, 34 in tumorigenesis and tumor suppression, 33, 35, 36, 37, 38 in development and reproduction, 39, 40 DNA damage, 41 and apoptosis and cell-cycle regulation. 33, 42, 43 In addition to regulating each other's function, 37, 44, 45 the functional outcome of these proteins are regulated by different mechanisms, including miRNAs, post-translational modifications, and protein–protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…[127][128][129] The more ancient members of the family include p73, involved in cancer, 130 neurodevelopment, 131,132 and aging, 133 and p63, involved in epidermal development, 119,[134][135][136] cancer, [137][138][139][140][141] reproduction, 142 and heart development. 143 Understanding the structural restrain of its structure is pivotal to understand the function of p53 [144][145][146] as well as its potential therapeutic exploitation. 147,148 The regulation of p53 protein half-life is crucial to his function 149,150 and, consequently, for cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Rodríguez-Marí et al 2010), medaka(Yasuda et al 2012) and spotted knifejaw testes 541 (Oplegnathus punctatus)(Du et al 2017), and the cytokine-cytokine interaction 542 pathway identified in Japanese flounder(Zhang et al 2015) and in zebrafish(Ribas et 543 al. 2017) gonads.…”
mentioning
confidence: 99%